Thucydides and the Corpus Lucianeum: How to Write History (Minerva, 2023)
The only historiographical treaty remaining from the Ancient World is How to Write History by Lucian of Samosata, where he analyses some of the mistakes made by contemporary historians. He also proposes some principles on how to write history. Effectively, Lucian suggests Thucydides’ model of writing history as a paradigm among that by other ancient historians. However, this use of Thucydides’ literary personality does not conform to the use that Lucian makes of Thucydides in his other works. It rather seems a way to authorize his own critique. This article examines this discrepancy in the light of the number and quality of quotes and references to Thucydides work in order to understand the real importance of this ancient historian in Lucian’s production, a writer who belongs to the Second Sophistic rhetorical school.
Keywords: Lucian; Thucydides; Rhetoric; Historiography; quotes